2021
DOI: 10.1177/01945998211047147
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Auditory Function in Young HIV‐Positive Adults With Clinically Normal Hearing

Abstract: Objective Little is known about peripheral auditory function in young adults with HIV, who might be expected to show early evidence of hearing loss if HIV infection or treatment does affect peripheral function. The goal of this study was to compare peripheral auditory function in 2 age- and gender-matched groups of young adults with clinically normal hearing with and without HIV. Study Design Matched cohort study with repeated measures. Setting Infectious disease center in Dar es Salaam, Tanzania. Methods Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…These results are consistent with our previous work in young adults, aged 20 to 30 years, 12 middle age adults, aged 37 to 49 years, 4 and HIV-positive children aged 1 to 18 years 15 living in Dar es Salaam, Tanzania. All previous studies found slightly, but reliably, smaller DPOAEs in HIV-positive individuals compared with HIV-negative individuals.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with our previous work in young adults, aged 20 to 30 years, 12 middle age adults, aged 37 to 49 years, 4 and HIV-positive children aged 1 to 18 years 15 living in Dar es Salaam, Tanzania. All previous studies found slightly, but reliably, smaller DPOAEs in HIV-positive individuals compared with HIV-negative individuals.…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesized subclinical decreases in peripheral auditory function in the CLWH due to HIV infection or treatment effects on auditory function according to our previous work in a young adult cohort. 12 Results from the current study are consistent with subtle but significant reductions in high frequency DPOAEs and ABR wave V amplitude in CLWH compared with an ageand sex-matched HIV-negative group. HIV-positive status was independently associated with approximately 0.4 to 3.8 dB lower DPOAE amplitudes at 6 and 8 kHz in both ears and approximately 0.28μV lower ABR wave V amplitudes in the right ear.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations